VO2/Si–Al gel nanocomposite thermochromic smart foils : largely enhanced luminous transmittance and solar modulation - Liu, C. (2014)
VO2 nanoparticles with a dimension of approximately 20nm were obtained by simple mechanical bead-milling method, which were well dispersed in transparent silica-alumina (Si-Al) gel matrix to form nanocomposites. The VO2/Si-Al gel thermochromic nanocomposite foils were fabricated with various VO2 solid contents and foil thickness. With 10% VO2 loading and 3μm foil thickness, high luminous transmittance (Tlum(20°C)=63.7% and Tlum(90°C)=54.4%), and large solar modulation ability (ΔTsol=12%) can be obtained which surpasses the best reported results (nanoporous films:Tlum(20°C)=43.3%, Tlum(90°C)=39.9% and ΔTsol=14.1%). This current approach provided a simple and scalable preparation method with the best combined thermochromic performance.